Feasibility of Achieving Nutritional Adequacy in Critically Ill Children with Critical Neurological Illnesses (CNIs)?-A Quaternary Hospital Experience - Marwa Mansour; Nicole Knebusch; Jennifer Daughtry; Thomas P. Fogarty; Fong Wilson Lam; Renan A. Orellana; Yi-Chen Lai; Jennifer Erklauer; Jorge A. Coss-Bu (MDPI AG, 2024)
The literature on the nutritional needs and outcomes of critically ill children is scarce, especially on those with critical neurological illnesses (CNIs). Current evidence shows a lower mortality in patients who achieve two-thirds of their nutritional needs during the first week of pediatric intensive care unit (PICU) admission. We hypothesized that achieving 60% of the recommended dietary intake during the first week of a PICU stay is not feasible in patients with CNI. We designed an observational retrospective cohort study where we included all index admissions to the PICU in our institution of children (1 month to 18 years) with CNI from January 2018 to June 2021. We collected patient demographics, anthropometric measures, and caloric and protein intake (enteral and parenteral) information during the first week of PICU admission. Goal adequacy for calories and protein was defined as [(intake/recommended) × 100] ≥ 60%. A total of 1112 patients were included in the nutrition assessment, 12% of whom were underweight (weight for age z score < −2). Of this group, 180 met the criteria for nutrition support evaluation. On the third day of admission, 50% of the patients < 2 years achieved caloric and protein goal adequacy, compared to 25% of patients > 2 years, with p-values of 0.0003 and 0.0004, respectively. Among the underweight patients, 60% achieved both caloric and protein goal adequacy by day 3 vs. 30% of non-underweight patients with p-values of 0.0006 and 0.002, respectively. The results show that achieving 60% of the recommended dietary intake by days 5 and 7 of admission was feasible in more than half of the patients in this cohort. Additionally, children who were evaluated by a clinical dietician during the first 48 h of PICU admission reached higher nutrition adequacy.